Caught in the crossfire: biodiversity conservation paradox of sociopolitical conflict - Bona Abigail Hilario-Husain; Krizler Cejuela Tanalgo; Sarrah Jane C. Guerrero; Francisco Gil N. Garcia; Tessie E. Lerios; May Eva Z. Garcia; Renee Jane Alvaro-Ele; Meriam Manampan-Rubio; Sedra A. Murray; Lothy F. Casim; Jamaica L. Delos Reyes; Kier Celestial Dela Cruz; et al. (npj Biodiversity)
Abstract The current state of global biodiversity is confronted with escalating threats arising from human-induced environmental changes and a growing array of unpredictable challenges. However, effective conservation efforts are often hindered by limited knowledge, especially in developing economies such as the Philippines. The limitations imposed by these shortfalls in biodiversity knowledge hamper the capacity to protect biodiversity in light of the continuing extinction crisis. Our study revealed that areas with higher conflict levels exhibited lower species richness, fewer occurrence records, and reduced forest cover. This finding provides initial evidence for the relationship between sociopolitical conflict and biodiversity in the Philippines. We posit that the security risks caused by sociopolitical conflicts could have a negative impact on conservation efforts, particularly in terms of monitoring and implementing measures to protect natural resources. The links that bind armed conflict and biodiversity conservation are multifaceted and complex issues that warrant greater scientific and political attention. Finally, we identified 10 meaningful approaches to address shortfalls in biodiversity knowledge in conflicted areas, particularly incorporating conflict-sensitive approaches, considering the geopolitical context and conflict dynamics to adapt and align their strategies with local realities for more effective conservation efforts.